Effects of Different levels of Zinc in the Performance and Meat Zinc Contents of Broilers - Bulao, Maria Fe S.; Acda, Sonia P.; Sanchez, Geraldine C. (JPAIR Multidisciplinary Research, 2013)
Zinc is one of the most deficient microminerals. For poultry, NRC (1994) recommended 40 ppm only but, commercial feeds contain more than 100 ppm resulting to toxicity. Zinc oxide is commonly used inorganic forticant but, its safety is questionable compared to organic counterpart. Generally, the study aimed to determine the effects of different levels of zinc oxide and zinc methionine in the performance of broilers and their meat content at 36 and 42 days. To address the latter, two experiments (experiment 1, zinc oxide and experiment 2, zinc methionine) were conducted and gathered data were analysed using ANOVA. Results showed that in both experiments, the performance and meat zinc contents were not affected but, the parts were affected showing highest zinc content in the liver, followed by the thigh and legs, and the wings. Lowest amount was noted in the breast. Fortification, up to 36 days of feeding was found to be enough. In fortification programs, it is recommended to use organic minerals.